Observations of the 2008 Kasatochi volcanic SO2 plume by CARIBIC aircraft DOAS and the GOME-2 satellite - Heue, Klaus-Peter; Brenninkmeijer, C. a. M.; Wagner, T.; Mies, K.; Dix, B.; Frieß, Udo; Martinsson, B. G.; Slemr, F.; Van Velthoven, P. F. J. (Atmospheric chemistry and physics, 2010)
The 2008 Kasatochi volcanic eruption emitted ≈1.5-2.5 Tg SO2 into the upper troposphere and lower stratosphere. Parts of the main volcanic plume (gases and particles) reached central Europe a week after the eruption and were detected there by the CARIBIC (Civil Aircraft for Regular investigation of the Atmosphere based on an Instrument Container) flying observatory. The plume was also observed by the GOME-2 satellite instrument, only a few hours after the CARIBIC aircraft had crossed the plume, thus giving a unique opportunity to compare results. Trajectories and local wind speeds are investigated in detail using the GOME-2 and CARIBIC observations for better comparison of the results from these two observational systems. A comparison of the satellite spatial pattern with the local observations of the wind speed and the trajectory model TRAJKS showed a slight discrepancy, which has to be considered for satellite validation. Hence, it appears that detailed analyses of wind speeds are required. Emitted and secondary particles, partly measured and sampled by the CARIBIC in situ instruments, affected the DOAS SO2 measurements, of both CARIBIC and GOME-2. Overall GOME-2 and the CARIBIC SO2 measurements agree very well. The major uncertainties remain the actual wind speed needed to properly correct for the advection of the plume between the different overpass times and effects of aerosols on DOAS retrievals. The good agreement can be seen as validation for both GOME-2 and CARIBIC DOAS observations.
Gesehen am 10.05.2023
Die 2 in SO2 im Titel ist tiefgestellt